Guilty people - Smith, Abbe (New Brunswick : Rutgers University Press, 2019)
Criminal defense attorneys protect the innocent and guilty alike, but, the majority of criminal defendants are guilty. This is as it should be in a free society. Yet there are many different types of crime and degrees of guilt, and the defense must navigate through a complex criminal justice system that is not always equipped to recognize nuances. In Guilty People, law professor and longtime criminal defense attorney Abbe Smith gives us a thoughtful and honest look at guilty individuals on trial. Each chapter tells compelling stories about real cases she handled; some of her clients were guilty of only petty crimes and misdemeanors, while others committed offenses as grave as rape and murder. In the process, she answers the question that every defense attorney is routinely asked: How can you represent these people? Smith's answer also tackles seldom-addressed but equally important questions such as: Who are the people filling our nation's jails and prisons? Are they as dangerous and depraved as they are usually portrayed? How did they get caught up in the system? And what happens to them there? This book challenges the assumption that the guilty are a separate species, unworthy of humane treatment. It is dedicated to guilty people--every single one of us.
Petty criminals -- Ordinary felons -- Rapists -- Murderers -- Guilty clients, guilty lawyers -- Index.
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Criminal justice, Administration of -- United States; Defense (Criminal procedure) -- United States; Justice pénale -- Administration -- États-Unis.; Défense (Procédure pénale) -- États-Unis.; LAW / General; Criminal justice, Administration of; Defense (Criminal procedure); United States; guilt, guiltiness, justice system, criminals, court cases, petty criminals, criminal defense attorneys, innocent, innocence, criminal defendants, crimes, degrees of guilt, misdemeanors, murder, rape, jail, prison, guilty people, law, law school, criminology, sociology, psychology, criminal law practice, criminal law, ethics, crime, punishment, race, poverty, the legal system, criminal lawyers, sex offenders, mass incarceration, free society, Guilty Project, Guilty Lawyers, criminal law cartoons, lock up one of 'em, some of my best friends are murderers; Electronic books